Perlindungan Hukum Kekayaan Intelektual (KI) Jenis Merek Dagang PADA Usaha Kecil Mikro Menengah (UMKM) menurut Undang-Undang No. 20 Tahun 2016 tentang Merek dan Indikasi Geografis - Masrifah, Masrifah; Apriani, Rani (Peneliti.net, 2025)
This research aims to understand the form of legal protection distributed by the state to brands in the MSME business sector. The author uses a normative legal research type research method that observes several legal norms, legal theories, which are synchronized with several sources of legal material, both from statutory regulations and other sources. The legal phenomenon that attracted the attention of the author until conducting this research was due to the mushrooming of the MSME sector, but business actors still put aside the interests of brand rights. Thus, based on research, if there are MSMEs that do not register their brand rights with the Director General of Intellectual Property (DJKI), their brand will not receive legal protection, and can be misused by other business actors in a detrimental manner.